PENGARUH SIKAP, PERSEPSI NILAI DAN PERSEPSI PELUANG KEBERHASILAN KOMPLAIN TERHADAP NIAT PENYAMPAIAN KOMPLAIN KONSUMEN DI HYPERMARKET SURABAYA - Anggraini, Imelda Citra (Kajian Ilmiah Mahasiswa Manajemen, 2013)
This study analyzes the factors that influence the intention of this study konsumen.Object grievance is consumen who have made complaints in Surabaya Hypermarket. Research problem refers to the phenomenon of the rise of hypermarkets in Surabaya and the development of existing technology. Therefore this research problem is the following: what influences consumers to submit complaints. The research objective was formulated to seek answers to the flow that affect consumer complaint intentions. Modeling is formulated in this paper aims to provide a critical understanding of the concept and measurement consumen.research complaints include perceptions of values, attitudes and perceptions towards complaints opportunities and success complaints as antecedents have significant consequences on customer complaints. In addition to a theoretical modeling, this study has formulated eleven hypotheses. Purposive method was chosen to obtain the required data in this study. The study used 147 respondents and all respondents are consumers Hypermarket in Surabaya. This research use Structural data analysis computer program Equation Model with Lisrel 8.80. Results of this study indicate that consumer alienation, experience and control consumer complaints have no effect on the perception of values, attitudes and perceptions of opportunities to complaints complaints success. But the perception of values, attitudes and perceptions towards complaints complaints affect the success chances of intention to complain.